Carboxypeptidase B2 and N play different roles in regulation of activated complements C3a and C5a in mice. (6th April 2018) - Morser, J.; Shao, Z.; Nishimura, T.; Zhou, Q.; Zhao, L.; Higgins, J.; Leung, L. L. K.
Abstract : Essentials Two basic carboxypeptidases are present in plasma, B2 (CPB2) and N (CPN). Cpb2 ‐/− and Cpn −/− mice were challenged in a hemolytic uremic syndrome (HUS) model vs. wild type. Cpb2 −/− exacerbates HUS while Cpn −/− exacerbates cobra venom factor challenge vs. wild type mice. CPB2 and CPN have overlapping but non‐redundant roles. Summary: Background: There are two basic carboxypeptidases in plasma. Carboxypeptidase B2 (CPB2) is activated from a circulating zymogen, proCPB2, and carboxypeptidase N (CPN) is constitutively active with both inactivating complement C3a and C5a. Aims: To test the roles of CPB2 and CPN in complement‐driven mouse models of cobra venom factor (CVF) challenge and hemolytic‐uremic syndrome (HUS). Methods: Cpb2 −/−, Cpn −/− and wild‐type (WT) mice were compared in an HUS model induced by Shiga toxin and lipopolysaccharide administration and following CVF administration. Results: HUS was exacerbated in Cpb2 −/− mice more than in Cpn −/− mice, compared with WT mice. Cpb2 −/− mice developed the HUS clinical triad of microangiopathic hemolytic anemia, uremia and thrombocytopenia. Treatment with anti‐C5 antibody improved survival of both Cpb2 −/− and Cpn −/− mice. In contrast, when challenged acutely with CVF, the reverse phenotype was observed. Cpn −/− mice had markedly worse disease than Cpb2 −/− mice, whereas the WT mice were resistant. Conclusions: CPN and CPB2 play overlapping but non‐redundant roles in regulating complement activation in vivo . The constitutively active CPN is key for inactivation of systemic C5a, whereas CPB2 functions as an on‐demand supplementary anaphylatoxin inhibitor in inactivating excessive C5a formed locally.